PWE-156 What is The Prevalence of Chronic Pancreatitis at Post Mortem? A Novel Approach Using "Digital Autopsy". (17th August 2016) - Campbell, JA; Sanders, DS; Howard, C; Hampton, J; Hopper, AD
Abstract : Introduction: The prevalence of exocrine insufficiency in patients with IBS type symptoms does not correlate with post mortem prevalence of chronic pancreatitis (CP) suggesting a failure of early diagnosis. Historical dissection post mortem studies estimate the incidence of chronic pancreatitis to be around 6–12%. "Digital autopsy" computerised tomography (CT) is a non-invasive alternative to conventional post mortem examination. We aimed to evaluate the prevalence of radiological changes of CP with this technique. Methods: Consecutive non-contrast post mortem CT scans were reviewed. Simple demographic information was collected (sex, age at death) as well as interval between death and scan. The presence of pancreatic calcification and/or atrophy was noted as radiological indicators of chronic pancreatitis. Main pancreatic duct anatomy was reviewed but smaller ductal changes were not assessed due to lack of intravenous contrast. Results: 124 scans were included for assessment (mean age 67.6 years, SD 18.6, 63.8% male). 9 scans were excluded due to inadequate pancreatic views (6 due to decomposition, 3 due to intra-abdominal fluid, lymphadenopathy or artefact). Scans were performed 0–14 days post mortem (median 2 days). 36/115 (32.1%) of those scanned had features of chronic pancreatitis. 20/115 (17.9%) had calcification, 26 (23.2%) had atrophy and 2 (1.8%) main pancreatic duct dilatation. There is a significant difference between average ages of those with (78 years) and without (62 years) radiological evidence of chronic pancreatitis (p < 0.0001) Conclusion: This is the first study to report the prevalence of chronic pancreatitis using post mortem CT. The prevalence seems to be higher when compared to conventional autopsy reporting. This could suggest an under diagnosis of early CP in clinical practice. Disclosure of Interest: None Declared